Sensory and physico-chemical properties and fatty acid profile of milk fortified with flaxseed oil - Veena, N; Surendra Nath, B; Laxman Naik, N; Sivakumar, S (Indian Journal of Dairy Science, 2017)
Flaxseed oil was incorporated in milk to enrich it with omega-3 fatty acids, especially, Î±-linolenic acid (ALA). The fortified milk was analyzed for their sensory and physico-chemical properties and fatty acid profile. Three different levels i.e., 0.4, 0.5 and 0.6% of flaxseed oil were added to milk and the level of addition was optimized on the basis of sensory and physico-chemical properties of the milk. Addition of flaxseed oil at 0.5% level did not significantly influence sensory and physico-chemical properties, which were comparable with control milk sample. Such an addition has also resulted in an increased ALA content. One serving (240 g) of fortified milk provides about 43.1% of recommended daily allowance of ALA i.e 1.6 g/day for male adults and 62.7% of 1.1 g/day for female adults.